MIMO Antenna with Notches for UWB System (MANUS). (18th June 2022) - Basir, Shahid; Alimgeer, Khurram Saleem; A Ghauri, Sajjad; Maqsood, Moazam; Sarfraz, Mubashar; Ali, Md Yeakub
Abstract : In this paper, a trinotch band MIMO antenna is designed for upper and lower WLAN (5.1 GHz, 5.5 GHz) i.e., (802.11a/g/n/ac/ax) and satellite X-band (8.5 GHz). The placement of closely found notches at 5.1 GHz and 5.5 GHz is addressed by taking advantage from the placement of the same notch elements at appropriate distances from each other, to split single resonance into biresonances. Similarly, the third notch is produced at 8.5 GHz via a U-shaped slot added in the antenna. 2x1-MIMO antenna with notch bands is expected with better isolation by analysis of co-configurations and cross-configurations.